The Relationship between Critical Thinking Skills and Akhlaqul Karimah in Elementary School Students - Subhan, Subhan (Journal of Integrated Elementary Education, 2025)
This study investigates the relationship between critical thinking skills and the practice of akhlakul karimah (noble character) among fifth-grade elementary students at Madrasah Ibtidaiyah Cokro Aminoto in Ambon, Indonesia. While akhlakul karimah is a core objective of Islamic education, the specific role of critical thinking in its development remains underexplored, particularly within the Indonesian primary education context. Using a quantitative approach, this research employed a psychological scale to measure the critical thinking skills and akhlakul karimah of 61 students. The findings indicate that students' akhlakul karimah is in a "good" category (mean score of 83.21), while their critical thinking skills are categorized as "fairly good" (mean score of 57.87). A significant positive correlation was found between the two variables (r=0.331, p<0.05), with slot deposit 5000 critical thinking contributing 10.9% to the students' akhlakul karimah. Other factors influence the remaining variance (89.1%). These results suggest that fostering critical thinking is an important, though not exclusive, strategy for enhancing students' moral character. The study's implications highlight the need for educational interventions that integrate critical thinking into moral education curricula to better support the development of noble character in students.